TOLERANSI MASYARAKAT MULTIETNIK DESA WAYABULA KECAMATAN MOROTOI SELATAN BARAT - Abbas, Irwan; Abdullah, Jainudin; Waliyulah Mahmud, Waliyulah Mahmud (Universitas Khairun, 2023)
The background of this research is that the rampant conflicts that occur can cause changes in attitudes of tolerance in the life of a multiethnic society. The purpose of this study is (1) to describe the tolerance of multiethnic communities in Wayabula Kecematan Village, South West Morotai, (2) To find out the models of tolerance of multiethnic communities in Wayabula Kecematan Ã‚Â Village, South West Morotai, and (3) To find out the factors that support and hinder the tolerance of multiethnic communities in Wayabula Kecematan MorotaiÃ‚Â Selatan Barat Village.Ã‚Â Ã‚Â The research method is a Ã‚Â type of case study research with a qualitative approach. Ã‚Â Observational Ã‚Â data collection techniques, interviews, and documentation. Ã‚Â Data analysis techniques are data Ã‚Â reduction, data presentation, and drawing conclusions.Based on the results of the study, it was concluded that (1) The tolerance of multiethnic communities in Wayabula village is carried out by forming mutual respect, mutual respect and not disturbing the differences shared by other individuals. In the sense that an attitude of tolerance can foster peace, prosperity in the life of a plural society, especially the people in Wayabula village who have plurality in a society that forms a multiethnic society. Wayabula Village is one of the villages in the South West Morotai district inhabited by multiethnic communities including Gorontalo, Galela, Javanese, Sanger, and Bugis. In the daily life of this multiethnic society leads a fairly safe, peaceful, peaceful life and there is never any conflict between ethnicities in people's lives, (2) Models of tolerance in a multiethnic society can start from a simple understanding that tolerating is the same as understanding and respecting the attitudes and behaviors of others. Understanding and respecting the behavior of others who have the same religious background as us is not easy, let alone applied to different people in everything. (3) In forming tolerance in multiethnic societies does not always work well, every process carried out sometimes has supporting factors and inhibiting factors in fostering community tolerance. The factor supporting the tolerance of multiethnic communities is an attitude of mutual acceptance, mutual respect, mutual respect, and mutual help to help the community. The inhibiting factor is the lack of awareness in people's lives in accepting differences and the lack of understanding of the importance of tolerance in society.